2020
DOI: 10.1186/s12931-020-01374-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223 plays a protecting role in neutrophilic asthmatic mice through the inhibition of NLRP3 inflammasome

Abstract: Background: Neutrophilic subtype asthma occurs in approximately 15-25% of the asthma cases and is associated with severe airflow obstruction, corticosteroid resistance. MicroRNA plays a vital role in regulating many immune processes, but how miRNA circuits coordinate airway inflammation during neutrophilic asthma is unclear. Methods: To investigate the molecular mechanism of miR-223 in regulation of neutrophilic airway inflammation, miR-223 knockout mice were used to the OVA/CFA-induced neutrophilic asthma or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 66 publications
1
28
1
Order By: Relevance
“…However, some have been studied more in depth, showing a high potential as future therapeutic tools through their up- or downregulation. In this sense, miR-146a ( 79 , 89 ), miR-21 ( 113 , 116 ), miR-150 ( 109 ), miR-145-5p ( 131 , 148 ), miR-320d ( 132 , 144 ), miR-155 ( 62 ) miR-223 ( 211 ), or miR-3162-3p ( 212 ) seem to hold promise as future elements in the therapeutic repertoire for COPD and asthma, respectively, some of which are common for both pathologies such as miR-146a ( 213 – 215 ) or miR-21 ( 54 , 62 ).…”
Section: Clinical Advances In the Use Of Mirnasmentioning
confidence: 99%
“…However, some have been studied more in depth, showing a high potential as future therapeutic tools through their up- or downregulation. In this sense, miR-146a ( 79 , 89 ), miR-21 ( 113 , 116 ), miR-150 ( 109 ), miR-145-5p ( 131 , 148 ), miR-320d ( 132 , 144 ), miR-155 ( 62 ) miR-223 ( 211 ), or miR-3162-3p ( 212 ) seem to hold promise as future elements in the therapeutic repertoire for COPD and asthma, respectively, some of which are common for both pathologies such as miR-146a ( 213 – 215 ) or miR-21 ( 54 , 62 ).…”
Section: Clinical Advances In the Use Of Mirnasmentioning
confidence: 99%
“…In macrophages, polarization states differ in terms of miR-223 expression; M2 polarization shows increased expression of miR-223, while in M1 polarization, miR-223 is downregulated [ 42 ]. Furthermore, miR-223 was previously shown to negatively regulate NLRP3 inflammasome activation in vitro and in vivo [ 11 , 43 , 44 ]. It was also recently reported that miR-223 directly targets NLRP3 inflammasome to reduce LPS-induced inflammatory responses [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, accumulating data has suggested that miR-223 plays an important role in various diseases, especially respiratory disease [20,38,39]. MiR-223 plays a key role in regulating the immune in ammatory response to neutrophil asthma by inhibiting the NLRP3/ IL-1β [40]; pharmacological blockade of the miR-223-NLRP3-IL-1β signaling axis alleviates acute respiratory distress syndrome [41]. In addition, the expression level of miR-223 has dramatically altered by other bacterial infections, For instance, gastric in ammation caused by Helicobacter pylori infection through induction of miR-223-3P expression in a Helicobacter pylori CagA-dependent manner [42]; the expression of miR-223 in the breast tissue of dairy cows with Streptococcus agalactis mastitis increased three-fold, which may be involved in the signal pathway of Streptococcus agalactis-induced mastitis [40].…”
Section: Discussionmentioning
confidence: 99%